Validation of a continuous infusion of low dose Iohexol to measure glomerular filtration rate: randomised clinical trial - Dixon, John J (J Transl Med, 2015)
INTRODUCTION: There is currently no accurate method of measuring glomerular filtration rate (GFR) during acute kidney injury (AKI). Knowledge of how much GFR varies in stable subjects is necessary before changes in GFR can be attributed to AKI. We have designed a method of continuous measurement of GFR intended as a research tool to time effects of AKI. The aims of this crossover trial were to establish accuracy and precision of a continuous infusion of low dose Iohexol (CILDI) and variation in GFR in stable volunteers over a range of estimated GFR (23-138 mL/min/1.73 m(2)). METHODS: We randomised 17 volunteers to GFR measurement by plasma clearance (PC) and renal clearance (RC) of either a single bolus of Iohexol (SBI; routine method), or of a continuous infusion of low dose Iohexol (CILDI; experimental method) at 0.5 mL/h for 12 h. GFR was measured by the alternative method after a washout period (4–28 days). Iohexol concentration was measured by high performance liquid chromatography/electrospray tandem mass spectrometry and time to steady state concentration (Css) determined. RESULTS: Mean PC was 76.7 ± 28.5 mL/min/1.73 m(2) (SBI), and 78.9 ± 28.6 mL/min/1.73 m(2) (CILDI), p = 0.82. No crossover effects occurred (p = 0.85). Correlation (r) between the methods was 0.98 (p < 0.0001). Bias was 2.2 mL/min/1.73 m(2) (limits of agreement −8.2 to 12.6 mL/min/1.73 m(2)) for CILDI. PC overestimated RC by 7.1 ± 7.3 mL/min/1.73 m(2). Mean intra-individual variation in GFR (CILDI) was 10.3% (p < 0.003). Mean ± SD Css was 172 ± 185 min. CONCLUSION: We hypothesise that changes in GFR >10.3% depict evolving AKI. If this were applicable to AKI, this is less than the 50% change in serum creatinine currently required to define AKI. CILDI is now ready for testing in patients with AKI. TRIAL REGISTRATION: This trial was registered with the European Union Clinical Trials Register (https://www.clinicaltrialsregister.eu/), registration number: 2010-019933-89.